Pengaruh Kinerja dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Unit Terminal Inpection Service di Bandara Internasional Soekarno - Hatta - Masdon Simarmata; Hodi (MES Bogor, 2024)
Terminal Inspection Service still often experiences problems with flight service performance and quality due to many reasons for service such as lack of officer training, inadequate equipment, lack of supervision, less effective policies. The aim of this research is to determine the influence of performance and service quality simultaneously on customer satisfaction at the terminal inspection service unit at Soekarno – Hatta Internasional Airport.The approach used in this research is quantitative. Quantitative research is a method in which the research data is in the form of 2 numbers and is analyzed using statistics to test the hypotheses that have been set. Based on the results of the hypothesis test, the t test shows that performance influences customer satisfaction, and the results of the t hypothesis test show that service quality influences customer satisfaction at the terminal inspection service unit. Based on the results of the coefficient of determination test, the R square (R2) value is 0.804. shows that performance and service quality variables have an effect of 80.4% on passenger satisfaction. This shows that the independent variables performance and service quality have a big influence on customer satisfaction at the Terminal Inspection Service unit at Soekarno - Hatta International Airport.